Dynamic Observation of the Three-Dimensional Distribution of Labeled Liposomes Using the Novel High-Resolution Single-Photon Emission Computed Tomography - Andreas Wirrwar; Doris Buchholz; Oliver Gottschalk; Sandra Viehöver; Nils Uwe Schramm; Hans-Wilhelm Müller (Molecular Imaging)
The aim of this study was to show that the multipinhole technique (high-resolution single-photon emission computed tomography [HiSPECT]) is suitable for dynamic imaging of both biodistribution and temporal uptake behavior of radiolabeled cationic liposomes in Balb/c-mice. HiSPECT uses multipinhole collimators adapted to a clinical SPECT scanner, together with a dedicated iterative reconstruction program. This technique provides both high spatial resolution and an improvement in sensitivity. Six male Balb/c mice received 9.8 ± 4.0 MBq of the In 111-labeled liposomes. The measurements started directly after the injection and tomographic data were acquired in steps of 5 minutes. The regional evaluation displayed a high initial uptake of liposomes in the lungs (45.4%), which decreased to 25.1% after 30 minutes and to below 2% after 48 hours. In contrast, liver uptake increased in the first 30 minutes from 13.1 to 21.2% and remained relatively stable at 24.4% (24 hours) and 18.8% (48 hours). The data are interpreted as a slow shift of liposomes from the lungs into the liver and later to other organs such as the spleen and bladder. This study shows that the HiSPECT technique is capable of dynamically visualizing the uptake behavior of radioactively labeled liposomes in vivo with high temporal and spatial resolution.